Getting it right : how working mothers successfully take up the challenge of life, family, and career - Zappert, Laraine T. (Pocket Books New YorkUS, 2001)
Seeks to address the issues of excellence, balance and basic sanity for professional women. Explores professional women's struggles with regard to motherhood; career success and family; and, finding the right partner. Draws on the experience of other professionals and provides insights, advice, and strategies for balancing the work-life equation.